The investments : an American conspiracy - Berube, Clair T. (Information Age Publishing, Inc., 2020)
"This book examines American societal structures and institutions, beginning and ending with public education, and exposes how dysfunction and the investment in this dysfunction is an actual political agenda. The Investments focuses on the capitalization, privatization and dismantling of public education, and how other social systems such as for-profit prisons, healthcare (or the lack thereof), racism and current immigration issues, the investment in criminalizing people called "the other", and the military/industrial complex are all co-dependent and symbiotic. At the Nexus of it all is American public education. An educated population threatens the status quo, so the pipeline between public education and other social institutions is real. Each has a toxic connection and reliance to each other. Each chapter will delve into the rigging that takes place to purposefully attempt to cripple public education and consciously create a permanent underclass, usually without the knowledge of the general public; and the egos, identities and sinister political forces behind such manipulation. Education is the hub of this book: because public education is the best vehicle for democracy America has ever known, and therefore, unbeknownst to many Americans, in the crosshairs. There is a vast conspiracy for power and control going on in our country; and many Americans are ignorant of the conspiracy. This book pulls back the curtain on the investment some in power have made in their efforts to create a permanent underclass in American society." --publisher description.